Modeling the change in the maximum temperature in Shahat region for the period 1961-2099 using SDSM technique - Almlean, Gama; bin Saeid, Sharaf ULdeen bin Saeid; Al Ghafoud, Abdul Rahman ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
The study aims to know the future of the climate in Libya according to the predictions of General Circulation Models (GCMs) that with average values in large ranges, where the need arose to adopt a system of rang Downsizing techniques in order to convert the climate outputs derived from GCMs to the values based on one meteorological station. In order to achieve the purpose of the study, the researcher uses the analytical quantitative method which fits the study phenomenon, so the Statistical Downscaling Model (SDSM) of the daily maximum temperatures was applied at the meteorological station of Shah at in north-eastern Libya, and the maximum temperatures were predicted for the period (2011 - 2040) (2041-2070) (2071-2099) under different scenarios (A2a) and (B2a). Through this, the magnitude of the variation in the maximum temperature of the Shahat meteor station became clear from month to month and from one scenario to another in relation to the base period (1961-1990).